The Effect of Environmental, Social, and Governance (ESG) Disclosure and Retention Ratio on Company Size in Companies Listed on the Indonesia Stock Exchange in 2022-2024 - Euis Mufahamah; Rahyono Rahyono; Rengga Desca Saputra; Safira Azzahra; Nanda Rahmadani; Siti Musyafa'ah (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to examine the influence of environmental, social, and governance (ESG) disclosure and retention ratios on company size. Sample selection was carried out using the purposive sampling method, which is a sampling technique from a number of populations based on certain criteria so that the selected sample is in accordance with the research objectives. The population in this study is energy sector companies listed on the Indonesia Stock Exchange in 2022-2024. The number of samples obtained was 8 energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024, so the number of observations was 24 data. The data sources used in this study come from the official website of the Indonesia Stock Exchange and the websites of related companies. This study uses a quantitative approach with data collection techniques using descriptive analysis and multiple linear regression analysis, and utilizes SPSS 25 software to process data. The results of the analysis show that ESG disclosure and retention ratio have no effect on company size. These findings indicate that these factors have not been the main determinant of the size of energy sector companies in Indonesia in the study period. This research is expected to contribute to the development of literature related to ESG and retention ratios in Indonesia and become a consideration for company management and investors in strategic decision-making.